Key contents of health education and their impact on improving medication adherence among hypertensive patients: A systematic review and meta-analysis - Mustara, Mustara; Hartono, Hartono; Pamungkasari, Eti P. (Narra Sains Indonesia, 2025)
Hypertension is a global health issue with significant effects on morbidity and mortality, and medication adherence is crucial for effective management. Despite its importance, adherence remains low among hypertensive patients. Health education has been shown to improve medication adherence, though its effectiveness varies across studies. The aim of this study was to systematically synthesize evidence on the impact of health education in enhancing medication adherence among hypertensive patients. This study followed preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines and employed the population, intervention, control, and outcome (PICO) approach to develop keywords for a search across five databases: Emerald, ProQuest, PubMed, ScienceDirect, and Scopus. All randomized control trials published between 2019 and 2024 in English, evaluating health education's impact on medication adherence in hypertensive patients aged ≥18 years were included. The protocol was registered on PROSPERO (CRD42024532890), and study quality was assessed using the CEBMa scale. Twelve high-quality articles (CEBMa score of ≥7) involving 1,827 participants were included, identifying four key themes in health education for hypertension: an overview of hypertension and complications, medication and side-effect management, healthy lifestyle modification, and medication adherence strategies. Health education significantly improved medication adherence by 33% (risk ratio (RR): 1.33; 95%CI: 1.08–1.64; p=0.008), with a medium-large effect on improving medication adherence (d=0.70; 95%CI: 0.34–1.05; p<0.0001) and a small-medium effect on reducing non-adherence (d=-0.45; 95%CI: -0.66–(-0.24); p<0.0001). Health education delivered 1 to 3 months and with individualized approaches showed better adherence outcomes compared to more than three months and group-based methods. Face-to-face education was more effective than the digital method. In conclusion, health education improves medication adherence in hypertensive patients when delivered comprehensively over 1–3 months through individualized face-to-face sessions. These findings support its integration as a key strategy in hypertension management to enhance adherence.